2020
DOI: 10.1039/d0en00748j
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic and immunomodulatory effects in human white blood cells after ex vivo exposure to polystyrene nanoplastics

Abstract: Accumulation of plastic and its derivatives, micro- and nanoplastics (MNPLs), is a substantial environmental and ecological problem that could potentially become a serious health concern to humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 48 publications
2
42
0
Order By: Relevance
“…These differences might be due to the inherent characteristics of the cell model used. For instance, our group used different white blood cell types to assess the effects of ex vivo exposures on several toxicity biomarkers, and the results show that, albeit all the cell lineages presented toxic effects, there were substantial differences among each target cell type [14]. Nonetheless, all these reports evaluate the effects of nanoplastic on a short time window, while adverse effects on human health could also rise due to the accumulation of nanoplastics following continuous exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These differences might be due to the inherent characteristics of the cell model used. For instance, our group used different white blood cell types to assess the effects of ex vivo exposures on several toxicity biomarkers, and the results show that, albeit all the cell lineages presented toxic effects, there were substantial differences among each target cell type [14]. Nonetheless, all these reports evaluate the effects of nanoplastic on a short time window, while adverse effects on human health could also rise due to the accumulation of nanoplastics following continuous exposure.…”
Section: Discussionmentioning
confidence: 99%
“…While some previous studies have found higher levels of DNA damage in samples treated with PSNPs, others have recorded no genotoxic or oxidative DNA damage associated with PSNPs exposure. On the one hand, one study observed DNA damage in half of the lymphocytes treated with PSNPs after acute exposure, while another one shows that PSNPs' genotoxic damage depends on the white cell lineage analyzed [14,39]. On the other hand, another study reported differences in the genotoxic effects observed in human lung cancer and macrophage cells after acute exposure to differently functionalized PSNPs particles [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arsenic is a well-known genotoxic compound and one of its most studied mechanisms of action is the induction of ROS and oxidative stress [45]. In addition, plenty of those studies reporting adverse effects of MNPLs have detected increased ROS levels and DNA damage after short-term exposures [10][11][12]46]. Concordantly, with the analysis of the long-term effects of the exposure to PSNPLs, As III , and PSNPLs/As III we found a signi cant increase in the total and oxidative DNA damage when compared with passage-matched AsTC (see Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Mouse embryonic broblasts phenotypically sensitive to oxidative damage, and previously transformed by 30 weeks of continuous sodium arsenite (As III ) exposure (2 µM) [30], were used in this study and will be henceforth referenced as arsenic-transformed cells (AsTC). AsTC were grown in DMEM medium supplemented with fetal bovine serum, as previously reported [12].…”
Section: Cell Culture Conditionsmentioning
confidence: 99%